Nutritional factors and survival in a cohort of patients with myelofibrosis - Buscemi, Silvio; Colombrita, Piero; Santoro, Marco; Randazzo, Cristiana; Buscemi, Carola; Barile, Anna Maria; Caruso, Roberta; Lombardo, Martina; Mancuso, Salvatrice; Gambino, Orazio; Bazan, Giuseppe; Siragusa, Sergio (Frontiers in Nutrition, 2025)
IntroductionMyelofibrosis (MF) is classified among the chronic myeloproliferative neoplasms and presents unique nutritional challenges. Inflammation can trigger metabolic changes that lead to malnutrition and, ultimately, cachexia. Splenomegaly, which may occupy much of the abdomen and compress the stomach, can cause early satiety and further contribute to malnutrition. We investigated associations between nutritional parameters, clinical features, and survival in individuals with MF.MethodsForty-five individuals with MF (21 males, 24 females) were included and compared with a healthy control group of 351 individuals (157 males, 194 females). Body composition (bioelectrical impedance analysis), resting metabolic rate (RMR), and substrate oxidation (indirect calorimetry) were assessed.ResultsThe mean follow-up was 31 ± 8 months, during which seven deaths occurred. MF was associated with malnutrition; patients exhibited lower bioelectrical phase angle values and higher RMR (32.4 ± 4.2 vs. 28.5 ± 3.6 kcal/kg-fat-free mass/24 h; p < 0.001) compared with controls. Kaplan–Meier survival curves showed that a phase angle (PA) below the median was associated with a lower survival rate (p < 0.005). Similarly, spleen length above the median was linked to poorer survival (p < 0.05).DiscussionNutritional factors may serve as important predictors of survival in individuals with MF and should be considered in future supportive interventions aimed at improving both survival and quality of life.